Negotiating race in stand-up comedy: interpretations of 'single story' narratives. (4th May 2017) - DeCamp, Elise
ABSTRACT: This paper explores how narratives of personal experiences among audience members in Midwestern comedy clubs shape their receptivity to the racial discourses deployed by stand-up comedians. Conducting a Midwest-based ethnography of comedy clubs located across three states, I collected data through a variety of methods, which included: live stand-up performance observations; interviews of comedians and audience members from the same shows to better situate their respective strategies and reactions; and audience surveys. My analysis reveals how the subtlety and art of stand-up performance styles combine with the pleasurable medium of humor to alternately reinscribe, challenge, or proudly celebrate audience understandings of race. The accounts shared by comedians and audience members at these clubs demonstrate the potential for stereotype humor – contingent on presentation styles and audience experiences – to foster ethnic solidarity or complicate racial-behavioral associations through repeated encounters with comedians who either indirectly challenge or actively critique familiar types.